EFFECT OF MRIDWEEKADI KASHAYA SEKA IN RETINAL HAEMORRHAGES ASSOCIATED WITH NON-PROLIFERATIVE DIABETIC RETINOPATHY – A CLINICAL STUDY (International Journal of Ayurveda and Pharma Research, 2021)
Diabetic retinopathy (DR) is a leading cause of acquired vision loss in middle-aged and elderly people globally. In modern science, other than the meticulous control of diabetes there is no proven non-invasive management for the prevention or cure of Diabetic retinopathy.In this study, mild to moderate Non-proliferative diabetic retinopathy (NPDR) with retinal haemorrhages is considered as a Timira (symptomatically) and as Abhishyanda (considering etiopathogenesis) with Kapha-pitta predominance. Mridweekadi kashaya, predominantly Kapha Pitta samana, was selected for the study to be used as Seka. Method: The study design was Interventional- pre and post evaluation without control, sample size fixed as 30 eyes. Mridweekadi kashaya was used as Seka for 21 days, twice daily. Fundus photographs were taken prior to commencement of Seka, on the 22nd day and then on 30th and 60th day after completion of the procedure. Change in extent of retinal hemorrhages were assessed as visualized in Fundus photographs and direct ophthalmoscopy. Change in visual acuity was assessed by LogMar Visual acuity chart and change in contrast sensitivity by Pelli-Robson contrast sensitivity chart consecutively, prior to the treatment, on the 10th day, 22nd day and then on 30th and 60th day after completion of procedure. Statistical analysis was done using Wilcoxon signed rank test and Paired t test according to the variable.Result: Control in retinal haemorrhages associated with NPDR and improvement in visual acuity and contrast sensitivity.Conclusion: Mridweekadi kashaya seka is effective in controlling retinal haemorrhages associated with NPDR.